Multivariate optimization for simultaneous determination of aspirin and simvastatin by reverse phase liquid chromatographic method using AQbD approach - Kalpana G. Patel; Apeksha T. Patel; Purvi A. Shah; Tejal R. Gandhi (Faculty of Pharmacy, Cairo University, 2017)
The present study describes the development of a robust method for the separation of aspirin and simvastatin using reverse phase high performance liquid chromatographic method on Kintex reverse phase C18 column (5Â Î¼m, 250Â mmÂ ÃÂ 4.6Â mm) with UV detection at 234Â nm. Box-Behnken design was applied for multivariate optimization of the experimental conditions of RP-HPLC for obtaining desired chromatographic resolution with limited number of experiments. Risk assessment was performed to identify the critical method parameters. Three independent parameters; volume of acetonitrile, molarity of buffer and flow rate were used to design mathematical models and study the in depth effects of these independent factors on various responses. The optimized and predicted condition consisted of acetonitrile and potassium dihydrogen orthophosphate buffer pH 2.9 adjusted with orthophosphoric acid (83.89:16.11,Â v/v) as mobile phase at a flow rate of 0.93Â ml/min. Using these optimum conditions, baseline separation of both drugs with good resolution and a run time of less than 6Â min was achieved. Perturbation plot revealed that the most important factor affecting the selected responses was volume of acetonitrile. Percent recoveries in terms of accuracy for both drugs at all three levels was found in the range of 99.15â101.86%. The pooled % relative standard deviation values for repeatability and intermediate precision studies was found to be less than 2% for both drugs. Hence, a robust, simple, accurate and reproducible high performance liquid chromatographic method was developed and validated and could be applied for routine quality control testing. Keywords: Aspirin, Simvastatin, Box-Behnken design, HPLC